1999
DOI: 10.1017/s0031182098003898
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the biological characteristics of two isolates of Neospora caninum

Abstract: This study compared the biological and genetic properties of a bovine (NC-SweB1) and a canine (NC-Liverpool) isolate of Neospora caninum. A mouse model for CNS infection demonstrated marked differences in pathogenicity between the isolates. NC-Liverpool induced severe clinical signs of neosporosis in 57/58 mice including discoordinated movement, hindlimb paralysis and coat ruffling with severe weight loss. In contrast NC-SweB1 induced similar but less severe symptoms in a much smaller proportion of mice over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 11 publications
3
62
0
3
Order By: Relevance
“…Western blot analyses revealed immuno-dominant pattern of 17; 29-32; 35-37 a 46 kDa with minor differences in two serum samples. Similar profiles were described by Álvarez-García et al (2002) and Atkinson et al (1999) who identified six major proteins in the range of 17-62 kDa. Cabaj et al (2005) detected specific antibodies against a wide range of NC-1 tachyzoite antigens from 9.5 to 58 kDa in the blood of European bison.…”
Section: Discussionsupporting
confidence: 88%
“…Western blot analyses revealed immuno-dominant pattern of 17; 29-32; 35-37 a 46 kDa with minor differences in two serum samples. Similar profiles were described by Álvarez-García et al (2002) and Atkinson et al (1999) who identified six major proteins in the range of 17-62 kDa. Cabaj et al (2005) detected specific antibodies against a wide range of NC-1 tachyzoite antigens from 9.5 to 58 kDa in the blood of European bison.…”
Section: Discussionsupporting
confidence: 88%
“…The kinetics of IgG1 and IgG2a production also showed a similar profile to the rates of antibody production in mice infected with Nc-Liv and Nc-1 isolates (Collantes-Fernández et al 2006a), namely the predominance of IgG2a and IgG1 responses for the early and chronic phase of infection, respectively. These results indicate that Nc-Goiás 1 is apparently less virulent than some isolates obtained from clinically affected animals, such as Nc-SweB1, Nc-Liv and Nc-1 (Atkinson et al 1999, Collantes-Fernández et al 2006a). This was also described for other isolates obtained from …”
mentioning
confidence: 73%
“…Biological characterisation of different laboratory-isolates of N. caninum has shown extensive genetic diversity (Schock et al 2001;Regidor-Cerrillo et al 2006 and significant variations in their in vivo pathogenicity and in vitro growth characteristics (Atkinson et al 1999, Schock et al 2001, Miller et al 2002, Pérez-Zaballos et al 2005, Collantes-Fernández et al 2006a. Despite this, most of these laboratoryisolates have been obtained from either cattle or dogs with clinical signs, stillbirth calves, or bovine aborted foetuses (Dubey et al 2007).…”
mentioning
confidence: 99%
“…A utilização desses animais, como um instrumento de análise laboratorial, torna-se uma importante ferramenta para estudos de patogenia, testes de produção e proteção vacinal, diagnóstico da enfermidade, estudos no desenvolvimento de medicamentos eficazes para o controle e tratamento da enfermidade ou, ainda, para determinar virulência dos isolados de campo (ATKINSON et al, 1999, QUINN et al, 2002.…”
Section: Resultsunclassified